Limitations of a Short Demographic Questionnaire for Bedside Estimation of Patients’ Global Cognitive Functioning in Epilepsy Patients - Gorny, Iris; Krause, Kristina; Albert, Anita; Schneider, Sabrina; Möller, Leona; Habermehl, Lena; Strzelczyk, Adam; Rosenow, Felix; Hermsen, Anke; Knake, Susanne; Menzler, Katja (Frontiers in Neurology, 2018)
Objectives: The German socio-demographic estimation scale was developed by Jahn et al. (2013) to quickly predict premorbid global cognitive functioning in patients. So far, it has been validated in healthy adults and has shown a good correlation with the full and verbal IQ of the Wechsler Adult Intelligence Scale in this group. However, there are no data regarding its use as a bedside test in epilepsy patients. Methods: Forty native German speaking adult patients with refractory epilepsy were included. They completed a neuropsychological assessment, including a nine scale short form of the German version of the WAIS-III and the German socio-demographic estimation scale by Jahn et al. (2013) during their pre-surgical diagnostic stay in our center. We calculated means, correlations and the rate of concordance (range +/-5 and +/-7.5 IQ score points) between these two measures for the whole group, and a sub-sample of 19 patients with a global cognitive functioning level within one standard deviation of the mean (IQ score range 85-115) and who had completed their formal education before epilepsy onset. Results: The German demographic estimation scale by Jahn et al. (2013) showed a significant mean overestimation of the global cognitive functioning level of 8 points in the epilepsy patient sample compared to the short form WAIS-III score. The accuracy within a range of +/-5 or +/- 7.5 IQ score points for each patient was similar to that of the healthy controls reported by Jahn et al. (2013) in our sub-sample, but not in our whole sample. Conclusion: Our results show that the socio-demographic scale by Jahn et al. (2013) is not sufficiently reliable as an estimation tool of global cognitive functioning in epilepsy patients. It can be used to estimate global cognitive functioning in a subset of patients with a normal global cognitive functioning level and who have completed their formal education before epilepsy onset, but it does not reliably predict global cognitive functioning in epilepsy patients in general, who often do not fulfill these criteria. It is therefore not a useful tool to be implemented in the general neuropsychological presurgical evaluation of epilepsy patients.